2016
DOI: 10.1038/srep39167
|View full text |Cite
|
Sign up to set email alerts
|

Possible Source Populations of the White-backed Planthopper in the Greater Mekong Subregion Revealed by Mitochondrial DNA Analysis

Abstract: The white-backed planthopper, Sogatella furcifera (Horváth) (Hemiptera: Delphacidae), is a serious pest of rice in Asia. However, little is known regarding the migration of this pest insect from the Greater Mekong Subregion (GMS) including Cambodia, Laos, Myanmar (Burma), Thailand, and Vietnam, into China’s Yunnan Province. To determine the migration patterns of S. furcifera in the GMS and putative secondary immigration inside China’s Yunnan Province, we investigated the population genetic diversity, genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
1
17
2
Order By: Relevance
“…Only two dominant COI haplotypes widely exist in all populations suggesting a high-level gene ow among them. Among the 11 COI haplotypes identi ed, four haplotypes, including the two dominant haplotypes, were also found by previous study [8]. Our study results demonstrate that the haplotype diversity was lower in Shandong Province than that in the GMS, which may be a consequence of founder events during migration.…”
Section: Genetic Diversity Of Wbphsupporting
confidence: 75%
“…Only two dominant COI haplotypes widely exist in all populations suggesting a high-level gene ow among them. Among the 11 COI haplotypes identi ed, four haplotypes, including the two dominant haplotypes, were also found by previous study [8]. Our study results demonstrate that the haplotype diversity was lower in Shandong Province than that in the GMS, which may be a consequence of founder events during migration.…”
Section: Genetic Diversity Of Wbphsupporting
confidence: 75%
“…For example, most insects have a high dispersal ability and thus high gene flow between different populations. This is especially true in migratory insects (Li et al, ; Yin et al, ) and is obviously different from the empirical analysis used on plant populations. In addition, many other factors including demographic history, intrinsic life‐history traits, and overall population characteristics should also be considered (Nazareno et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…The immigration sources into Yunnan Province during April to early May were estimated to be mainly from Myanmar, while the mid-May immigrations originate from northern Vietnam 6 , 12 . Recently, we have used the mitochondrial cytochrome oxidase I (mtCOI) marker to determine the sources and patterns of the WBPH in the GMS 13 , demonstrating that the potential emigration of the WBPH from the GMS consists of three possible major routes. Those results not only confirmed that the immigration sources of the WBPH into China’s Yunnan Province were from Myanmar, Vietnam, and Laos 6 , 12 , 14 , but also indicated that Cambodia was a likely additional migration source.…”
Section: Introductionmentioning
confidence: 99%